Pengaruh Level Protein Pakan pada Masa Pertumbuhan terhadap Penampilan pada Awal Peneluran Ayam Betina Hasil Persilangan Ayam Kampung Jantan dan Ayam Ras Petelur Betina (Jurnal Ilmu dan Teknologi Hasil Ternak, 2017)
This research aims to examine the effects of various dietary protein levels during growing period crossbreed hens between cockerel native chickens and laying hens on performance at onset of lay. The effects of the dietary protein levels on weight and other components of eggs were also examined. Eighteen hens aged thirteen weeks were randomly divided into three different treatment groups. Each group consists of six replications. The replication contains a hen. All the treatment hens were grown in a battery-cage until reaching sexual maturity then were fed with three different dietary protein levels which are 13,54%, 12,00%, and 9,80% formulated with 2600 kcal/kg ME. The collected data were analyzed by a one-way classification of variance analysis (CRD) followed by testing the significant means using The Duncan,s MultipleRange Test (DMRT). The experiment result suggested that the treatment during henâ€™s growing period did not cause significance on performance at onset lay, egg weight, and egg components weight.Â